Penggunaan LMS Google Classroom pada Materi Persamaan dan Pertidaksamaan Linear Satu Variabel Kelas VII (Indonesian Journal of Science, Technology, Engineering, Art, and Mathematics Education, 2023)
To support educational goals and facilitate the learning process, a media is needed so that it can achieve learning goals. The purpose of this study was to find out the use of LMS google classroom on material linear equations and inequalities for one class VII variable. The approach used in this research is descriptive qualitative research. In the implementation of the LMS using the Problem Based Learning learning model. Subjects between 10 class VII students (control) in class and 10 students VII (experimental) in a Google classroom at the UPTD school of SMP Negeri 1 Kalabahi. Judging from the results of the N-Gain score of 10 students in class VII (control) in the N-Gain class the score was 0.35141122 at the Criterion level of "Medium" N-Gain level. While the results of the percentage of the N-Gain score, namely 35.14112204, are in the "Less Effective" N-Gain Effectiveness Interpretation Category and the N-Gain results of 10 students VII (experimental) in the Google classroom, namely 0.664, are in the "Medium" N-Gain level Criteria. While the results of the percentage of N-Gain score, namely 66.4, are in the "Quite Effective" N-Gain Effectiveness Interpretation Category.